2013
DOI: 10.1136/bjsports-2013-092298
|View full text |Cite
|
Sign up to set email alerts
|

Fit and healthy Paralympians—medical care guidelines for disabled athletes: a study of the injuries and illnesses incurred by the Polish Paralympic team in Beijing 2008 and London 2012

Abstract: In both PGs, illnesses were more frequent than injuries. RTIs presented a serious problem. Some groups of disabled athletes are at an increased risk of injury/illness. The more stringent medical care guidelines before London may have caused staggeringly better results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…A separate study [18] describing injuries in 91 Polish Paralympians in Beijing (2008) and 100 in London (2012) reported an incidence rate of 29.8/1000 athlete‐days (95% CI 22.1‐37.6) in Beijing and only 15/1000 athlete‐days (95% CI 9.0‐21.0) in London. Three studies examining injury in elite Brazilian visually impaired athletes recorded longitudinal data during the period 2004‐2008 in 3 separate sports but sample size is small and limited to one nation [1,3].…”
Section: Who Is Affected By Injury?mentioning
confidence: 99%
“…A separate study [18] describing injuries in 91 Polish Paralympians in Beijing (2008) and 100 in London (2012) reported an incidence rate of 29.8/1000 athlete‐days (95% CI 22.1‐37.6) in Beijing and only 15/1000 athlete‐days (95% CI 9.0‐21.0) in London. Three studies examining injury in elite Brazilian visually impaired athletes recorded longitudinal data during the period 2004‐2008 in 3 separate sports but sample size is small and limited to one nation [1,3].…”
Section: Who Is Affected By Injury?mentioning
confidence: 99%
“…Observations of Gawroński et al (2013) also confirm the impact of physical examinations on decreasing the number of diseases and musculoskeletal injuries during the London PG compared to the Beijing PG as a result of the rigorous execution of PPE before the summer PG in 2010. The results regarding winter sports athletes show a similar trend, i.e.…”
Section: Discussionmentioning
confidence: 61%
“…This was probably due to the implementation in the Polish national team, in the form of enforcing before the Games, preventive multispecialist examinations in the field of sports medicine. Such a procedure was recognized not only by the Paralympic Games, but also proved to be effective in reducing the incidence of musculoskeletal injuries and illnesses during the Paralympic Games [18]. Therefore, it may be suggested that similar medical measures should be introduced at a club level.…”
Section: Discussionmentioning
confidence: 99%
“…Blauwet and Iezzoni, Wedgwood and Calvente Rejón [11,16,17] emphasised the need for understanding and acceptance of sport for people with disabilities, especially in the environment of athletes with disabilities. Gawroński et al and Simon and Ward highlighted the importance of care and specialized medical staff in the process of training of athletes with disabilities [18,19]. Furthermore, diagnosis of injuries, including those dangerous to health, and appropriate treatment to ensure the return to sport are also essential [20].…”
Section: Introductionmentioning
confidence: 99%